Knowledge Management: Determine the Influencing Factors for Practicing at the Libraries in Bangladesh - Mamun, Mostofa; Othman, Roslina; Zulkifli, Zahidah (Journal of Education Culture and Society, 2023)
Aim. The main objective of this research is to know the influencing factors for KM practices in the library field of Bangladesh from the user’s point of view. Therefore, the study examines the elements influencing Knowledge Management (KM) practice in Bangladeshi university libraries. Methods. Present research used a quantitative approach, by adopting printed survey questionnaire for data collection from the users of the University of Dhaka (DU) and the University of Rajshahi (RU) in Bangladesh. Statistical software IBM®-SPSS® was used for data analysis, and the "partial least squares" (PLS) method was used to test the proposed hypothesis. Results. The findings revealed that KM familiarity and perceptions in gender and current study level varied across users. This study found that all the proposed hypotheses are supported, i.e., the service quality and critical success factors are the most influencing factors for practicing KM in the DU and RU library. Conclusions. The findings provide valuable insights regarding awareness about KM practices and assist university authorities in formulating relevant policies and taking necessary actions for KM practices in libraries. Originality. The present research is one of the first research in Bangladesh that identified the influencing factors of KM from the user’s point of view.